PENGARUH LOCUS OF CONTROL DAN KOMPETENSI TERHADAP KINERJA KARYAWAN DENGAN BUDAYA ORGANISASI SEBAGAI PEMODERASI PADA PT. TELKOMSEL BRANCH SIDOARJO - Susanti Prasetiyaningtiyas; Rizky Atika Salsabila Ivabianca Putri; Dewi Prihatini (VALUE: Journal of Business Studies, 2022)
Locus of control and competency are factors that can affect employee performance. Organizational culture is one of the factors that can strengthen or weaken influence so that it acts as a moderating variable. This study aims to determine the influence of Locus of Control and Competence on Employee Performance and the influence of organizational culture in moderating the influence of Locus of Control and Competence on Employee Performance. This research is explanatory research with 42 respondents. Sampling using non-probablity sampling method with purposive sampling technique. The data analysis method used is Moderated Regression Analysis. The results showed that Locus of Control and Competence has a positive and significant impact on employee performance. Organizational Culture is proven to moderate the influence of Locus of Control on employee performance and moderate the effect of Competence on Employee Performance at Telkomsel Branch Sidoarjo. Implementation of organizational culture in building employee self-management and competence is important in improving employee performance.